Analysis of the Clinicopathological Characteristics, Genetic Phenotypes, and Prognostics of Primary Pulmonary and Bronchial Adenoid Cystic Carcinoma - Zhengyang Hu; Xing Jin; Jian Wang; Qihai Sui; Yanjun Yi; Dejun Zeng; Zhencong Chen; Qun Wang; Jiacheng Yin; Lin Wang; Zongwu Lin (Thoracic Cancer)
ABSTRACT Background Primary pulmonary and bronchial adenoid cystic carcinoma (PACC) is a rare, low‐grade malignant tumor of the lung. However, the relationship between its clinical features, surgical prognosis, and genetic phenotype has not been fully described. Methods PACC patient information was collected from the SEER, TCGA, and Zhongshan Hospital, Fudan University (FDZSH) databases. Overall survival (OS) was evaluated using the Kaplan–Meier method. Univariate and multivariate analyses through Cox proportional hazards regression identified risk factors that predicted OS. The limma and matfools packages from R were used to compare the differential genes and mutations between PACC and LUAD, respectively. Results Two hundred and ninety‐two patients, 14 patients, and 12 patients with PACC were identified from the SEER, TCGA, and FDZSH databases, respectively. The 3‐, 5‐, and 10‐year OS of the PACC patients were 91.7%, 88.6%, and 85.0%, respectively, compared to 95.8%, 93.9%, and 93.3% for patients who underwent surgery. Race, pathological grade, M stage, regional node examination, and regional node positive were independent prognostic factors for the OS of patients who underwent surgery. The gene map of PACC and lung adenocarcinoma (LUAD) shows significant differences. Common mutations found in lung cancer were almost undetectable in PACC patients, whereas mutations in the NOTCH pathway were more common. TMB levels and PD‐1/PD‐L1 expressions were also lower in PACC patients. Conclusion Our study analyzed the main factors that influence the prognosis of PACC patients undergoing surgery and discovered the unique genetic phenotype of PACC.